LEGAL FORCE OF BINDING SALE PURCHASE AGREEMENT UNDER HAND REVIEWED FROM THE PRINCIPLE OF PACTA SUNT SERVANDA - Bianty, Thisia; Gunadi, Ariawan (DE LEGA LATA: JURNAL ILMU HUKUM, 2025)
The Sale and Purchase Agreement is basically an assistance agreement that functions as a preliminary agreement and is free in form . In the making of PPJB in practice in the field, it is found that it is not uncommon for the parties to enter into a PPJB underhand as a preliminary agreement containing several agreements and there have also been many PPJB underhand there is a default from one of the parties who promised . This scientific article uses deductive analysis, as well as normative research types. PPJB made underhand is an agreement made by the parties themselves without any intervention from authorized public officials, and without a specific standard and only adjusted to the needs of the parties . If the parties do not deny and acknowledge their signatures in the agreement, then the PPJB underhand has legal force based on the principle of pacta sunt servanda.